The new Penguin opera guide - Holden, Amanda (Penguin, 2001)
The New Pengiun Opera Guide" is a fully revised and updated edition of the most comprehensive single-volume opera encyclopaedia ever published. In the course of hundreds of meticulously researched articles, it explores the complete operas of figures as diverse as Bellini and Britten, Handel and Hindemith, Massenet and Monteverdi, Rameau and Rossini, Weber and Weill; offers fresh insights into such perennial favourites as Mozart, Verdi and Wagner; and examines stage works by composers not primarily remembered for their operas - Schumann, Faure and Schoenberg among them. It also brings the reader right up to date with the latest operas by contemporary composers worldwide, including Ades, Carter, Holliger, Macmillan, Picker, Reich, Saariaho and Tan Dun. In all it discusses nearly 850 composers and looks in detail at around 2,000 works. For every composer, there is an outline of their operatic career and an assessment of their contribution to the genre. Each of their significant operatic works has its own entry, with information about the libretto, duration, cast and orchestra, the background to the work, the plot, and musical highlights. Selected recordings are included, to guide the reader towards the best versions, and there is also information about publishers and available editions, as well as bibliographical references. Each article has been written by a leading expert in the field, for example, Tim Carter on Monteverdi, Philip Gossett on Rossini, David Cairns on Berlioz, Roger Parker on Puccini, Michael Kennedy on Richard Strauss, John Tyrrell on Janacek, Stephen Walsh on Stravinsky. For the enthusiast or novice, amateur or professional, "The New Penguin Opera Guide" is an ideal source of information and insight. It brings alive the entire rich and varied tapestry of opera, from its beginnings four hundred years ago right up to the present day.